Red pigment in Bacillus megaterium spores. - Mitchell, C (1986)
Bacillus megaterium QM B1551 spores contained a unique red pigment in their membranes that was not found in other species. This red pigment, presumably a carotenoid, was synthesized about the time of dipicolinic acid synthesis during sporulation and was associated with the forespores. A yellow pigment was synthesized during sporulation in rich medium and was found in the mother cell compartment. Although the yellow pigment was also associated with spores, it could be removed by two different extraction procedures without impairing germination; it was absent when sporulation occurred in a minimal medium. Although the yellow pigment of the mother cell appeared to be dispensable, the red pigment may serve a more critical function, such as membrane stabilization.